2018
DOI: 10.11648/j.js.20180601.14
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Hernia Post Laparotomy-Incidence and Risk Factors

Abstract: Laparotomy incisions are one of the most common procedures performed in any surgical service. However, they carry certain risks like surgical site infections, wound dehiscence and incisional hernia. There have been various risk factors associated with the incidence of incisional hernia post laparotomy. Some of these factors are patients-related like history of diabetes, obesity, smoking, sex and age. The other factors are related to the disease process itself like emergency surgeries, presence of peritonitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It was thought that the stronger muscle structures of male patients compared to female patients and their exposure to more physical pain in the early postoperative period may play a role. It is known that bleeding and wound infection increase the development of IH after laparotomy which is performed for other reasons 20,21 . As a result of their meta‐analysis, Bulter et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was thought that the stronger muscle structures of male patients compared to female patients and their exposure to more physical pain in the early postoperative period may play a role. It is known that bleeding and wound infection increase the development of IH after laparotomy which is performed for other reasons 20,21 . As a result of their meta‐analysis, Bulter et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that bleeding and wound infection increase the development of IH after laparotomy which is performed for other reasons. 20,21 As a result of their meta-analysis, Bulter et al reported that among the patients who underwent LT, the risk of developing IH in patients with postoperative bleeding and wound infection during the follow-up increased. 22 According to the our results, we seen that male gender (p = .021), high BMI rate (p = .003), postoperative bleeding (p = .018), and wound infection (p = .039) as a risk factor on development of IH.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout time, complex abdominal wall defects have increased due to patients' possibility to overcome critical illness after laparotomy [15], presenting a new surgical challenge that requires a wide armamentarium of surgical techniques and approaches, seeking to provide a proper reconstruction, procedure, showing positive results, with less proportion of recurrence (< 4% in 12 months), postoperative complications (hematoma (<1%), seroma (<3%), surgical site infection (SSI) (<10%)) and an acceptable median length of hospitalization of 5.9 days [4,16].…”
Section: Discussionmentioning
confidence: 99%